2022
DOI: 10.3390/ijms232416108
|View full text |Cite
|
Sign up to set email alerts
|

Statins Show Anti-Atherosclerotic Effects by Improving Endothelial Cell Function in a Kawasaki Disease-like Vasculitis Mouse Model

Abstract: Kawasaki disease (KD) is an acute inflammatory syndrome of unknown etiology that is complicated by cardiovascular sequelae. Chronic inflammation (vasculitis) due to KD might cause vascular cellular senescence and vascular endothelial cell damage, and is a potential cause of atherosclerosis in young adults. This study examined the effect of KD and HMG-CoA inhibitors (statins) on vascular cellular senescence and vascular endothelial cells. Candida albicans water-soluble fraction (CAWS) was administered intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
(73 reference statements)
1
13
0
Order By: Relevance
“… 57 Another study with ApoE -/- mice showed that statins promotes eNOS expression and restores vascular endothelial cell function. 58 In summary, anti-aging effects of stains are mainly based on downregulation of oxidative stress and pro-inflammatory response while upregulation of eNOS expression that leads to enhanced NO bioavailability and improved endothelial function. Therefore, to determine whether the benefit effects of statins are directly related to PSCK9 inhibition, immunofluorescent staining was performed for the aging markers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“… 57 Another study with ApoE -/- mice showed that statins promotes eNOS expression and restores vascular endothelial cell function. 58 In summary, anti-aging effects of stains are mainly based on downregulation of oxidative stress and pro-inflammatory response while upregulation of eNOS expression that leads to enhanced NO bioavailability and improved endothelial function. Therefore, to determine whether the benefit effects of statins are directly related to PSCK9 inhibition, immunofluorescent staining was performed for the aging markers (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, it is important to understand the mechanisms beyond the positive impact on inflammation and coronary artery abnormalities. In a murine study, atorvastatin demonstrated anti-atherosclerotic effects by enhancing the function of endothelial cells in artificially induced Kawasaki-like vasculitis [42]. Motoji et al showed that the use of statins may be able to prevent the cardiovascular events associated with Kawasaki disease by stimulating the expression of endothelial nitric oxide synthase (eNOS), which restored the function of endothelial cells [42].…”
Section: Statins and Cardiovascular Disordersmentioning
confidence: 99%
“…Using vascular cells as an example, it has been shown that cellular senescence can be triggered by chronic inflammation. This ultimately leads to endothelial dysfunction, which promotes atherosclerosis [ 54 ] and other CVDs [ 55 ].…”
Section: Senescencementioning
confidence: 99%
“…Motoji et al [ 54 ] conducted a study in mice to test how vasculitis and statins affect cellular senescence and vascular endothelial cells. The study used atorvastatin at a dose of 10 mg/kg/day.…”
Section: Effects Of the Use Of Statins On The Process Of Cellular Sen...mentioning
confidence: 99%
See 1 more Smart Citation